The mediating factor of psychological well-being between cyberbullying experience and sedentary behaviour among university students - Nugroho, Purwo Setiyo; Samutachak, Bhubate; Jirapramukpitak, Tawanchai; Ghozali; Ahmad Fauzi, Fatimah; Chamratrithirong, Aphichat (Elsevier B.V., 2025)
The cyberbullying affects 45 % of young people, this situation highlights the burden of cyberbullying amidst advancement of technology/digital era in developing countries like Indonesia. This study revealed the mediating role of psychological well-being in the relationship between cyberbullying experiences and sedentary behaviour among university students in Indonesia. A cross-sectional survey was conducted with 700 undergraduates from Universitas Muhammadiyah Kalimantan Timur, using standardized measures of cyberbullying victimization, psychological well-being, coping capacity, and sedentary behaviour. Structural Equation Modelling revealed significant associations between cyberbullying experience and lower psychological well-being (β = 0.264, p ≤ 0.001), and between lower psychological well-being and sedentary behaviour (β = 0.208, p ≤ 0.001). Psychological well-being fully mediated the cyberbullying-sedentary behaviour relationship, with no direct link identified between these variables. Although coping capacity contributed independently to psychological well-being (β = 0.448, p ≤ 0.001), it did not moderate the cyberbullying-psychological well-being relationship as hypothesized. Model fit indices (X2 = 2782.212; SRMR = 0.071; X2/df = 3.56) were acceptable despite NFI concerns (0.760). These findings illuminate the mechanism through which digital victimization may influence physical activity patterns, highlighting the critical importance of psychological interventions in addressing the behavioural health consequences of cyberbullying among university students. Future research should explore these relationships longitudinally and investigate effective coping strategies.